C-reactive protein and vasospasm after aneurysmal subarachnoid hemorrhage1 - Romero, Flávio Ramalho; Cataneo, Daniele Cristina [UNESP]; Cataneo, Antonio José Maria [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2014)
PURPOSE:To evaluate the relationship between C reactive protein levels and clinical and radiological parameters with delayed ischemic neurological deficits and outcome after aneurysmal subarachnoid hemorrhage.METHODS:One hundred adult patients with aneurismal SAH were prospectively evaluated. Besides the baseline characteristics, daily C-reactive protein levels were prospectively measured until day 10 after subarachnoid hemorrhage. The primary end point was outcome assessed by Glasgow Outcome Scale, the secondary was the occurrence of delayed ischemic neurological deficits (DINDs).RESULTS:A progressive increase in the CRP levels from the admission to 3rd postictal day was observed, followed by a slow decrease until the 9th day. Hemodynamic changes in TCD were associated with higher serum CRP levels. Patients with lower GCS scores presented with increased CRP levels. Patients with higher Hunt and Hess grades on admission developed significantly higher CRP serum levels. Patients with higher admission Fisher grades showed increased levels of CRP. A statistically significant inverse correlation was established in our series between CRP serum levels and GOS on discharge and CRP levels.CONCLUSIONS:Higher C-reactive protein serum levels are associated with worse clinical outcome and the occurrence of delayed ischemic neurological deficits. Because C-reactive protein levels were significantly elevated in the early phase, they might be a useful parameter to monitor.
Keywords: C-Reactive Protein; Vasospasm, Intracranial; Subarachnoid Hemorrhage